Anatomske, kemijske in sorpcijske lastnosti beljave in jedrovine rdečega bora - Merela, Maks (Acta silvae et ligni, 2019)
In the case of Scots pine (Pinus sylvestris L.), anatomical differences between the sapwood and heartwood were researched, the content of extractives in the sapwood and heartwood defined, hygroscopicity of sapwood and heartwood studied, so as the relationship between the content of extractives and sorption properties. Research was carried out on 6 test trees. Anatomical investigations were performed using the classic light-field microscopy. Investigation of samples for determination of dimensional stability and sorption properties was held by conditioning in the glass-air condition chambers. Samples for chemical analysis were extracted with cyclohexane and a mixture of acetone and water, and the proportion of total phenols was determined by UV-Vis spectrophotometry. The differences between the sapwood and heartwood were in the resin canals, in the lumens of axial tracheids along the rays as well as differences in parenchymal cells and bordered pits. The content of extractives in the heartwood was higher than in the sapwood. Investigations of the sapwood and heartwood did not show statistically significant differences in the density in the absolutely dry state, at the point of saturation of cell walls, in the volume shrinkage, and not in the coefficient of swelling in the radial direction. We found differences between the sapwood and heartwood transverse anisotropy, differential swell in the tangential direction, in the coefficient of swelling in the radial direction and the sorption quotient. These differences can be attributed to mutual effect of the anatomical and chemical characteristics of both types of wood and when interpreting indicators
Keywords: anatomija lesa; beljava; ekstraktivi; extractives; heartwood; jedrovina; Pinus sylvestris L.; rdeči bor; sapwood; Scots pine; sorpcijske lastnosti; sorption properties; wood anatomy